STRATEGI MANAJEMEN RISIKO USAHATANI MELON DI LAHAN PASIR PANTAI KABUPATEN KULON PROGO - Yekti, Ananti (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2019)
Farmer play a role as a worker as well as a manager in his farm. As a manager, farmer has the function to managing risks and formulating strategies to minimize the risk impact. Objectives of this study were to: 1) know the perception of coastal sand farmers about farming risk 2) identify and analyse the risk management strategy that melon farmers have implemented; 3) formulate activity recommendation to reduce the impact of melon farm risk in coastal sand. The study was conducted in April - May 2014, with locations in District of Galur. Data used in the study were taken from 50 respondents, analysed descriptively referring to the model Jolly (1993) and Matlon (1991). The results showed that intercropping cultivation system, land rotation and crop rotation were ex-ante management strategies that farmers should take. An interactive risk management strategy that needs to be addressed is: selection of planting season, inorganic fertilization application and pesticide as well as the need to encourage labour gathering culture. Seeking crops with lower production risks becomes an alternative risk management ex-post in order to suppress further losses. Accessibility of farmers to formal financial institutions is known to be good.